2016
DOI: 10.1097/olq.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians' Adherence to Expert Recommendations for Cervical Cancer Screening and Prevention in the Context of Human Papillomavirus Vaccination

Abstract: Background Expert recommendations do not recommend using Pap or human papillomavirus (HPV) test results to determine whether unvaccinated females should receive HPV vaccine, nor do they recommend using vaccine receipt to inform cervical cancer screening practices. This study characterizes physicians’ HPV vaccine recommendations and practices in the context of HPV and Pap testing. Methods We surveyed family physicians and obstetrician-gynecologists randomly selected from the American Medical Association Maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Due to delayed initial screening, the lack of early diagnosis and the unavailable widespread screening by cervical cytology ( 2 ), cervical cancer mainly occurs in developing countries and causes approximately 265,000 deaths every year worldwide ( 3 ). In addition, approximately 85% of new cervical cancer cases occur in lower socioeconomic countries ( 4 ). Emerging studies indicate that risk factors, such as infection of high-risk types of human papillomavirus (HPV), promiscuity and early sexual intercourse, have essential effects on cervical cancer progression ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to delayed initial screening, the lack of early diagnosis and the unavailable widespread screening by cervical cytology ( 2 ), cervical cancer mainly occurs in developing countries and causes approximately 265,000 deaths every year worldwide ( 3 ). In addition, approximately 85% of new cervical cancer cases occur in lower socioeconomic countries ( 4 ). Emerging studies indicate that risk factors, such as infection of high-risk types of human papillomavirus (HPV), promiscuity and early sexual intercourse, have essential effects on cervical cancer progression ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies could exist between perceived and actual adherence to guidelines, as reported earlier by family medicine practitioners ( 20 ). Most previous surveys were based on the physician’s perspective and reported answers via recollection of their own habits ( 15 , 21 , 22 , 23 ); this could be affected by recall bias. Here, we took advantage of collecting data from two sources (physicians and patients): being asked about what one usually does implies an answer either on average or by archetype.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the relationship between HL and adherence to the recommendation to undergo breast cancer screening among Japanese women reported that breast and/or cervical cancer screening behavior is related to receiving a recommendation from a doctor and with having a primary care physician [29]. A study of primary care physicians' adherence to expert recommendations for cervical cancer reported that the specialty of obstetrician-gynecologist was associated with higher average adherence to cancer screening recommendations [30]. However, this is partly due to the lack of a general primary physician system in Japan.…”
Section: Discussionmentioning
confidence: 99%